FINANCIAL DISTRESS OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muhammad Fadila Laitupa; Hesty Indriani (Jurnal Ekonomi, 2023)
This study aims to analyze differences in levels of financial distress using the Zwimjweski method before and during Covid-19 in manufacturing companies listed on Bursa Efek Indonesia (BEI) for the 2019 and 2020 periods. This type of research is quantitative research using a purposive sampling technique which produces 133 samples. The research data collection technique uses documentation obtained from public company financial reports published on the IDX through the IDX's official website, namely www.idx.co.id. Then it was reviewed and tested using SPSS software version 25. The results of the T-Test analysis showed that there was no significant difference between the level of financial distress both before and during the Covid-19 pandemic. So it can be concluded that the average financial distress before and during the Covid-19 pandemic has a value that is not much different.